Why upright standing men urinate more efficiently than in supine position: A morphological analysis with real‐time magnetic resonance imaging. Issue 5 (14th April 2022) - Shimatani, Kimihiro; Soufi, Mazen; Sato, Yoshinobu; Yamamoto, Shingo; Kanematsu, Akihiro
Abstract: Purpose: Few studies have examined the effects of body position on urination efficiency morphologically. We aimed to dissect out the anatomical changes of pelvic organs during urination in the upright and supine positions by a real‐time magnetic resonance imaging (rtMRI) system. Methods: Thirteen healthy male volunteers aged 26–60 years were included in the study. The sagittal real‐time two‐dimensional images were taken to evaluate urinary efficiency, along with change in six morphological indices at the time of storage and the beginning of voiding, in both upright ant supine positions. Results: Urination was more efficient in upright position than in supine position, as expressed by higher average rate of bladder emptying (9.9 ± 4.2 vs. 6.8 ± 2.9 ml/s, p  < 0.05) and also by fewer participants showing significant residual urine (1/13 vs. 7/13, p  < 0.05). At the onset of voiding in standing position, the levator ani (LA) muscle moves downward and backward followed by descent of the bladder neck and rotation of the prostate around the symphysis. Such changes were expressed by two morphological indices. One was posterior vesicourethral angle at the start of voiding, 152 ± 7 versus 140 ± 1 in upright and supine position ( p  < 0.05). The other index was the change in angle between the LA line and pubo‐coccygeal line in upright and supine position, 9.4 ± 9.9 versus 1.6 ± 7.9 before voiding ( p  < 0.05) and 30.2 ± 14.0 versus 17.3 ± 12.9 after the start of voiding ( p  < 0.05). Conclusion: The dynamic relaxation of LA seemed to be a key movement that enables more efficient urination in standing position than in supine position.